2017
DOI: 10.1080/15384047.2017.1294292
|View full text |Cite
|
Sign up to set email alerts
|

Chronic inflammation confers to the metabolic reprogramming associated with tumorigenesis of colorectal cancer

Abstract: It's well known that microenvironment inflammatory signals could promote cancer development and progression. In colorectal cancer (CRC), chronic inflammation is a major driving mechanism for the development of CRC in patients having long-standing inflammatory bowel disease (IBD). Though it has been addressed that cancer cells ferment much of their glucose supply into lactate regardless of the presence of oxygen, it is unclear whether cell metabolism has been reprogramed during the process from IBD to CRC. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 16 publications
1
29
0
Order By: Relevance
“…Taking into account that cancer in many aspects resembles a state of chronic inflammation [ 46 ], cells representing the immune system, and in particular macrophages, play an important role as active elements of the reactive stroma [ 47 ]. The recruitment of macrophages into tumors is mediated by cytokines, chemokines, and growth factors originating from cancer and nearby normal tissue stroma.…”
Section: Reactive Cancer-associated Stromamentioning
confidence: 99%
“…Taking into account that cancer in many aspects resembles a state of chronic inflammation [ 46 ], cells representing the immune system, and in particular macrophages, play an important role as active elements of the reactive stroma [ 47 ]. The recruitment of macrophages into tumors is mediated by cytokines, chemokines, and growth factors originating from cancer and nearby normal tissue stroma.…”
Section: Reactive Cancer-associated Stromamentioning
confidence: 99%
“…To uncover the possible impact of AST on inflammation and glucose metabolism in vivo, a DSS-induced colitis mouse model was established. DSS is a well-known agent for inducing inflammation in order to identify the impact of inflammation on the pathogenesis and the clinical course of inflammation (18)(19)(20). In the DSS-induced colitis mouse model of the present study, compared with the combined treatment of AST and DSS, mice administered DSS alone were used as a positive control, and those with AST treatment alone served as a negative control.…”
Section: Ast Inhibits the Expression Levels Of Glycolytic Enzymes In mentioning
confidence: 99%
“…Others investigated how liver derived EVs modulate the serum metabolome; ex vivo exposure of serum to EVs from hepatocytes modified the serum metabolite content hypothetically through the enzymatic activity carried by EVs [74]. Together, these studies point at the potential relevance of EVs in metabolic disease, but also during tumour progression as cancer cells are known to rely on reprogramming during adaptation to their microenvironment [75,76]. Accordingly, we demonstrated that hypoxia results in increased glioma cell release of procoagulant EVs that could trigger endothelial cell activation in a paracrine manner [77], and that hypoxia-derived EVs mimic the hypoxic response of glioma tumour cells resulting in enhanced in vivo tumour angiogenesis and growth [78].…”
Section: Functional Roles Of Extracellular Vesicles and Lipoproteinsmentioning
confidence: 99%